A new fluorescence chemosensor for Zn2+ with a remarkable red shift in emission spectra. Issue 32 (2nd August 2017) - Azadbakht, Reza; Koolivand, Mostafa; Khanabadi, Javad
Abstract : A new fluorescent chemosensor with a remarkable red shift in emission spectra based on naphthalene groups for quantification of zinc ions was synthesized and investigated. Abstract : A new fluorescent chemosensor with a remarkable red shift in emission spectra based on naphthalene groups for quantification of zinc ions was synthesized and investigated. It was found that sensor H2 L exhibited a remarkably large red shift in emission upon complexation with Zn 2+ ions. The limit of detection (LOD) was calculated to be 4.98 × 10 −9 M. The fluorescence behavior of the prepared compound resembles with IMP and INH logic gates.